APPLICATION FOR fluorescent emission toxin detection Carcinogenic peeled chestnuts FOR EXPORT - Reátegui S., S. (2012)
The Brazil Nut Tree, Bertholettia excelsa, while providing a fruit rich in all kinds of nutrients for human health, contributes to environmental conservation. The temperature and humidity of the environment in which they grow and are harvested, coupled with inadequate management of fruits, at harvest, post harvest, processing and storage; favor fungal infection and the production of derivatives difuranocumarinas, known as the aflatoxins (AFs) B1, B2, G1 and G2 whose identification is derived by the blue and green color emitted from the fluorescence when exposed to UV light. In this paper, it has been evaluated the use of a UV excitation source as part of a system to recognize the fluorescence emitted by the Brazil Nut Tree; making the separation easier and faster from those which are contaminated by FAs. The selection by detecting fluorescent emission depends on the type of detectors and sensors used.